2013
DOI: 10.2337/db13-0247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion and Pharmacological Inhibition of Phosphodiesterase 10A Protects Mice From Diet-Induced Obesity and Insulin Resistance

Abstract: Phosphodiesterase 10A (PDE10A) is a novel therapeutic target for the treatment of schizophrenia. Here we report a novel role of PDE10A in the regulation of caloric intake and energy homeostasis. PDE10A-deficient mice are resistant to diet-induced obesity (DIO) and associated metabolic disturbances. Inhibition of weight gain is due to hypophagia after mice are fed a highly palatable diet rich in fats and sugar but not a standard diet. PDE10A deficiency produces a decrease in caloric intake without affecting mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Selective PDE10A inhibitors, such as SEP-39, are unlikely to produce the metabolic side effects seen with current antipsychotics, which are due to, in part, H1 antagonism. Furthermore, data in the literature suggest that PDE10A inhibitors protect against the effects of a high fat diet (Nawrocki et al, 2014) and may be insulinogenic (Cantin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Selective PDE10A inhibitors, such as SEP-39, are unlikely to produce the metabolic side effects seen with current antipsychotics, which are due to, in part, H1 antagonism. Furthermore, data in the literature suggest that PDE10A inhibitors protect against the effects of a high fat diet (Nawrocki et al, 2014) and may be insulinogenic (Cantin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP/PKA pathway is negatively regulated by phosphodiesterases (PDEs) that degrade cAMP. Pharmacological inhibition of PDE10A or deletion of PDE10A increases beige adipogenesis and energy expenditure in mice (115, 218). Furthermore, activation of α2 adrenergic receptors, unlike β adrenergic receptors, inhibits brown adipocyte thermogenesis (367).…”
Section: Neural Regulation Of Brown and Beige Fat Thermogenesismentioning
confidence: 99%
“…For example, cell-based studies (Walz et al, 2007), studies with PDE3B KO mice (Choi et al, 2006), and studies in transgenic mice overexpressing PDE3B in pancreatic b-cells (Harndahl et al, 2002) clearly establish a central role for PDE3B in regulation of insulin secretion. However, inhibition of PDE8B (Dov et al, 2008) and PDE10A (Nawrocki et al, 2014) also modulates insulin secretion. Recent studies in a murine model of diet-induced obesity have indicated that adiposity and weight gain was reduced and insulin sensitivity was improved in PDE10A KO mice or in WT mice treated with a PDE10 inhibitor (Nawrocki et al, 2014).…”
Section: Novel Targeting Approachesmentioning
confidence: 99%